2015
DOI: 10.2147/opth.s83162
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of prophylactic besifloxacin 0.6% and moxifloxacin 0.5% in patients undergoing cataract surgery

Abstract: BackgroundThe purpose of this study was to investigate the ocular bacterial flora in patients scheduled to undergo cataract surgery and compare the antibacterial effects of besifloxacin ophthalmic suspension 0.6% and moxifloxacin ophthalmic solution 0.5% in these patients.MethodsThis was a prospective, randomized, laboratory-masked clinical trial. Patients received besifloxacin or moxifloxacin “quater in die” or QID (four times a day) for 3 days before cataract surgery in the surgical eye and 1 hour before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Bucci et al [ 80 ] randomized 67 cataract surgery patients to receive besifloxacin or moxifloxacin before surgery to compare the FQs’ antibacterial efficacy. Patients instilled study drug four times a day for 3 days in the surgical eye and 1 h before surgery in the nonsurgical fellow eye, and bacterial load was assessed at the time of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Bucci et al [ 80 ] randomized 67 cataract surgery patients to receive besifloxacin or moxifloxacin before surgery to compare the FQs’ antibacterial efficacy. Patients instilled study drug four times a day for 3 days in the surgical eye and 1 h before surgery in the nonsurgical fellow eye, and bacterial load was assessed at the time of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the minimum inhibitory concentration (MIC) values for besifloxacin against Gram-positive pathogens are consistently lower, by at least two to three dilutions, than those for moxifloxacin and gatifloxacin against the same isolates [3][4][5], Pharmaceuticals 2021, 14, 517 2 of 13 and that besifloxacin was also the most rapidly bactericidal [6]. Besifloxacin ophthalmic suspension 0.6% (Besivance ® , Bausch + Lomb) has been studied clinically for the treatment of bacterial conjunctivitis [7][8][9][10][11][12][13][14] and other potential uses [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%